Barriers and opportunities to recruitment in mental health: the case of New Zealand. (1st December 2008) - Rasquinha, Desiree; Mouly, V. Suchitra; Hatcher, Simon; Sankaran, Jayaram K.
The New Zealand (NZ) Mental Health (MH) sector has expanded rapidly over the last decade, and questions have been posed about the capacity of the MH workforce to meet demand in the forthcoming years. Accordingly, this study examines the recruitment policies, practices, barriers and opportunities of the MH sector of NZ. We find that apart from international trends such as a global shortage in the MH workforce, domestic demographic patterns pose rather unique challenges for recruitment into the sector. These include the dispersion of a thin rural population across far-flung areas and the multi-cultural nature of NZ society. Within the sector, recruitment processes differ between District Health Boards (DHBs) and Non-Governmental Organisations (NGOs). Given the impact of diverse entities such as education providers and the media, a sector-wide approach to recruitment into the MH workforce is necessitated. The application of the principles of business process management to recruitment is also called for.